Method for improving fluidity of polycyclic aromatic hydrocarbon material

By preparing an activator solution coated with nano zinc oxide materials with amphoteric polymer and mixing it with the fused ring aromatic hydrocarbon material to form an emulsified solution, the problems of poor fluidity and insufficient stability of the fused ring aromatic hydrocarbon material are solved, and the fluidity and stability are significantly improved.

CN119823770APending Publication Date: 2025-04-15LIANYUNGANG PENGCHEN SPECIAL NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411958512.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing fused-ring aromatic hydrocarbon materials have poor fluidity, especially under low temperature conditions, and their stability needs to be further improved.

Method used

By preparing a good stability activator solution, the solution consists of an amphoteric polymer coated with nano zinc oxide material, dodecyl glucoside and sodium dodecyl benzene sulfonate, and added to the fused ring aromatic hydrocarbon material to form an emulsified solution to improve its fluidity and stability.

Benefits of technology

The fluidity and stability of the fused-ring aromatic hydrocarbon material are significantly improved, especially under low temperature conditions, and the stability of the emulsifier solution is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216496510000091
    Figure BDA0005216496510000091
Patent Text Reader

Abstract

The invention discloses a method for improving fluidity of a polycyclic aromatic hydrocarbon material. The method comprises the following steps: preparing an amphoteric polymer coated nano zinc oxide material; dispersing the amphoteric polymer coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecyl benzene sulfonate, performing ultrasonic treatment to obtain an activator solution, mixing the activator solution with a polycyclic aromatic hydrocarbon material, and performing ultrasonic treatment to obtain the polycyclic aromatic hydrocarbon material with high fluidity. The activator solution with good stability is prepared and added into the polycyclic aromatic hydrocarbon material to form an emulsified solution with good stability, so that the stability of the polycyclic aromatic hydrocarbon material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aromatic hydrocarbon material modification, and in particular to a method for improving the fluidity of condensed ring aromatic hydrocarbon materials. Background Art

[0002] With the rapid development of my country's petrochemical industry, the amount of heavy oil and other polycyclic aromatic materials in various refineries has increased significantly. Although the properties of heavy aromatics in various refineries are quite different, most polycyclic aromatic oils are still mixed with vacuum residue oil as fuel oil and have not been effectively utilized. Research has found that polycyclic aromatics can be widely used in oil refining, chemical industry and high-tech fields, and it has a very broad prospect for improving product yield, improving product quality and increasing economic benefits.

[0003] Polycyclic aromatic hydrocarbon materials are low in cost and are mainly used as plasticizers. They have good compatibility with general plastics. However, they have the following disadvantages when used as plasticizers: existing polycyclic aromatic hydrocarbon materials have high density and poor fluidity at room temperature. Therefore, in order to improve the application of polycyclic aromatic hydrocarbon materials, the fluidity of polycyclic aromatic hydrocarbon materials needs to be improved.

[0004] The patent with application number CN01138905.2 provides a diesel low temperature fluidity improver, which contains 10-70% ethylene-vinyl acetate copolymer, 5-50% vinyl acetate-fumarate copolymer, 1-40% fatty acid ester containing hydroxyl group, 1-30% oil-soluble fatty amide, and 1-40% low volatility and low viscosity ester solvent. The patent with application number CN02116293.X provides the components and proportions of 5-10 parts of polyoxypropylene polyoxyethylene propylene glycol ether, 5-10 parts of polyoxypropylene polyoxyethylene polyethylene polyamine ether, 1-5 parts of sodium dodecylbenzene sulfonate, 1-5 parts of polyoxypropylene polyoxyethylene resin ether, 1-3 parts of polyoxypropylene polyoxyethylene fatty alcohol ether, 1-3 parts of methanol and 30-50 parts of water, and then heat to 50-100°C, stir at constant temperature for 2 hours, and discharge the material when the temperature drops to 30-40°C to obtain the improver. Although the above-mentioned existing technologies can effectively reduce the viscosity of crude oil to a certain extent, the improvement effect under low temperature conditions is not obvious, and the stability also needs to be further improved. Summary of the invention

[0005] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for improving the fluidity of condensed aromatic hydrocarbon materials is provided. The present invention prepares an activator solution with good stability, which can be added to the condensed aromatic hydrocarbon material to form an emulsified solution with good stability, thereby effectively improving the stability of the condensed aromatic hydrocarbon material.

[0006] In order to solve the above technical problems, the technical solution of the present invention is:

[0007] A method for improving the fluidity of condensed aromatic hydrocarbon materials comprises the following steps:

[0008] (1) reacting a DMF solution of thionyl chloride with a DMF solution of SDBS in a reactor. After the reaction is completed, washing the reaction solution multiple times in an ice water bath, and then drying and removing the solvent to obtain dodecylbenzenesulfonyl chloride;

[0009] (2) dissolving dodecylbenzenesulfonyl chloride, triethylamine and diallylamine in dichloromethane, stirring for reaction, then washing the reaction product several times, and removing the solvent to obtain a functional monomer;

[0010] (3) dissolving acrylamide, sulfobetaine methacrylate and SDS in deionized water, and then adjusting the pH thereof to be neutral to obtain a first monomer solution, dissolving glycidyl methacrylate and the above functional monomer in DMSO to obtain a second monomer solution, adding nano zinc oxide and SDS into deionized water, stirring and emulsifying, to obtain a nanoparticle dispersion, mixing the above first monomer solution and the second monomer solution, and adding the above nanoparticle solution, introducing nitrogen into the above reaction system to replace the air, adding an initiator, and heating the reaction system under a nitrogen atmosphere for polymerization reaction; after the reaction is completed, cooling the reaction solution to room temperature and filtering it, washing the precipitate, and setting it aside;

[0011] (4) dispersing the washed precipitate in deionized water, adding 2-aminobenzimidazole, and reacting. After the reaction is completed, cooling to room temperature, filtering the reaction solution, washing the precipitate, and drying it to obtain an amphoteric polymer-coated nano zinc oxide material;

[0012] (5) dispersing the above-mentioned amphoteric polymer-coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecylbenzene sulfonate, and ultrasonically treating to obtain an activator solution, and mixing the above-mentioned activator solution with a polycyclic aromatic hydrocarbon material and ultrasonically treating to obtain a polycyclic aromatic hydrocarbon material with high fluidity.

[0013] Preferably, in step (1), the mass ratio of thionyl chloride to SDBS is (2-3): (6-10).

[0014] Preferably, in step (1), the reaction temperature is 5°C and the reaction time is 10-15h.

[0015] Preferably, in step (2), the mass ratio of dodecylbenzenesulfonyl chloride, triethylamine and diallylamine is (5-8): (6-7): (5-6).

[0016] Preferably, in step (2), the stirring reaction temperature is room temperature, the stirring speed is 500-1000 rpm, and the time is 10-15 h.

[0017] Preferably, in step (3), the concentrations of acrylamide, sulfobetaine methacrylate and SDS in the first monomer solution are 1-2 mmol / ml, 0.1-0.2 mmol / ml and 0.005-0.01 g / ml, respectively; the concentrations of glycidyl methacrylate and functional monomer in the second monomer solution are 0.02-0.05 mmol / ml and 0.02-0.05 mmol / ml, respectively; the concentrations of nano zinc oxide and SDS in the nanoparticle dispersion are 2-3 wt% and 0.01-0.05 wt%, respectively; and the volume ratio of the first monomer solution, the second monomer solution and the nanoparticle dispersion is 50:1:(5-10).

[0018] Preferably, in step (3), the initiator is a mixture of ferrous sulfate heptahydrate and 2,2'-azobis(2-methylpropionamidine) dihydrochloride, the mass ratio of the two being 1:(1-2); and the amount of the initiator added is 5-10% of the mass of acrylamide.

[0019] Preferably, in step (3), the temperature of the polymerization reaction is 55-65° C. and the time is 5-6 hours.

[0020] Preferably, in step (4), the amount of 2-aminobenzimidazole added is 3-6% of the mass of the precipitate, the reaction temperature is 75-85° C., and the reaction time is 2-5 h.

[0021] Preferably, in step (5), in the activator solution, the concentrations of the amphoteric polymer-coated nano zinc oxide material, dodecyl glucoside, and sodium dodecylbenzene sulfonate are 0.2-0.3 g / L, 0.1-0.2%, and 0.1-0.5%, respectively.

[0022] Preferably, in step (5), the volume ratio of the activator solution to the condensed aromatic hydrocarbon material is (9-10):1.

[0023] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0024] The invention uses AM, SBMA, self-made functional monomer N, N-diallyl-4-dodecylbenzenesulfonamide (DBDAP) ​​and glycidyl methacrylate (GMA) as monomers to in-situ synthesize an amphiphilic polymer on the surface of nano zinc oxide particles. The amphiphilic polymer is compounded with dodecyl glucoside and sodium dodecylbenzenesulfonate in a certain proportion to form an activator solution, which can form a stable emulsifier solution with condensed aromatic hydrocarbon materials, thereby improving the fluidity of the condensed aromatic hydrocarbon materials. DETAILED DESCRIPTION

[0025] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0026] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0027] It should be noted that the raw materials involved in the following embodiments and comparative examples, unless otherwise specified or specifically limited, can be commercially available products or can be prepared in-house according to existing public preparation processes; at the same time, the steps involved in the method, unless otherwise specified or specifically limited, can be carried out according to existing technologies or using existing equipment, and the present invention document will not describe them one by one.

[0028] Nano zinc oxide: The average particle size is 50nm.

[0029] Example 1

[0030] A method for improving the fluidity of condensed aromatic hydrocarbon materials comprises the following steps:

[0031] (1) 2.95 g of thionyl chloride and 25 ml of DMF were mixed, and then a mixed solution consisting of 6.96 g of SDS and 40 ml of DMF was added, and the mixture was reacted at 5° C. for 12 h. After the reaction was completed, the reaction solution was washed several times with dichloromethane in ice water and dried, and the solvent was removed to obtain dodecylbenzenesulfonyl chloride;

[0032] (2) 7 g of dodecylbenzenesulfonyl chloride, 6 g of triethylamine and 5 g of diallylamine were dissolved in 50 ml of dichloromethane, and the mixture was stirred at room temperature and 500 rpm for 12 h. The reaction product was then washed with a 1 wt % dilute hydrochloric acid solution, a 1 wt % sodium hydroxide solution and a saturated salt water solution for multiple times, and the solvent was removed to obtain a functional monomer;

[0033] (3) Dissolve acrylamide (AM), sulfobetaine methacrylate (SBMA), and SDS in 50 ml of deionized water (the concentrations of AM, SBMA, and SDS are 1.2 mmol / ml, 0.15 mmol / ml, and 0.005 g / ml, respectively), and then adjust the pH to neutral to obtain a first monomer solution. Dissolve glycidyl methacrylate (GMA) and the above functional monomers in 10 ml of deionized water. DMSO (the concentrations of GMA and functional monomers are 0.02mmol / ml and 0.02mmol / ml, respectively) is added to obtain a second monomer solution, nano zinc oxide and SDS are added to 50ml deionized water for stirring and emulsification (the concentrations of nano zinc oxide and SDS are 2wt% and 0.01wt%, respectively) to obtain a nanoparticle dispersion, the first monomer solution and the second monomer solution are mixed, and the nanoparticle solution is added (the volume ratio of the first monomer solution, the second monomer solution, and the nanoparticle dispersion is 50:1:5), nitrogen is introduced into the reaction system to replace the air, and an initiator of 6% of the mass of acrylamide (ferrous sulfate heptahydrate and 2,2'-azobis(2-methylpropionamidine) dihydrochloride are added in a mass ratio of 1:1) is added, the temperature is raised to 60°C under a nitrogen atmosphere, and the polymerization reaction is carried out for 5h; after the reaction, the reaction solution is cooled to room temperature and filtered, and the precipitate is washed and set aside;

[0034] (4) Disperse 2 g of the washed precipitate in 50 ml of deionized water, add 2-aminobenzimidazole (5% of the mass of the precipitate), react at 80° C. for 3 h, cool to room temperature after the reaction, filter the reaction solution, wash the precipitate with ethanol and dry it to obtain an amphoteric polymer-coated nano zinc oxide material;

[0035] (5) dispersing the above-mentioned amphoteric polymer-coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecylbenzene sulfonate, and ultrasonically treating at 500W for 30min to obtain an activator solution, in which the concentrations of the amphoteric polymer-coated nano zinc oxide material, dodecyl glucoside, and sodium dodecylbenzene sulfonate are 0.2g / L, 0.1%, and 0.4%, respectively;

[0036] (6) The activator solution and the polycyclic aromatic hydrocarbon material are mixed in a volume ratio of 9:1, and ultrasonically treated at a power of 500 W for 30 minutes to obtain a polycyclic aromatic hydrocarbon material with high fluidity.

[0037] Example 2

[0038] A method for improving the fluidity of condensed aromatic hydrocarbon materials comprises the following steps:

[0039] (1) 2.95 g of thionyl chloride and 25 ml of DMF were mixed, and then a mixed solution consisting of 6.96 g of SDS and 40 ml of DMF was added, and the mixture was reacted at 5° C. for 12 h. After the reaction was completed, the reaction solution was washed several times with dichloromethane in ice water and dried, and the solvent was removed to obtain dodecylbenzenesulfonyl chloride;

[0040] (2) 7 g of dodecylbenzenesulfonyl chloride, 6.4 g of triethylamine and 5 g of diallylamine were dissolved in 50 ml of dichloromethane, and the mixture was stirred at room temperature and 600 rpm for 12 h. The reaction product was then washed with 1 wt % dilute hydrochloric acid solution, 1 wt % sodium hydroxide solution and saturated brine for multiple times, and the solvent was removed to obtain a functional monomer;

[0041] (3) Dissolve acrylamide (AM), sulfobetaine methacrylate (SBMA), and SDS in 50 ml of deionized water (the concentrations of AM, SBMA, and SDS are 1.5 mmol / ml, 0.1 mmol / ml, and 0.008 g / ml, respectively), and then adjust the pH to neutral to obtain a first monomer solution. Dissolve glycidyl methacrylate (GMA) and the above functional monomers in 10 ml of deionized water. DMSO (the concentrations of GMA and functional monomers are 0.03mmol / ml and 0.03mmol / ml, respectively) is added to obtain a second monomer solution, nano zinc oxide and SDS are added to 50ml deionized water and stirred for emulsification (the concentrations of nano zinc oxide and SDS are 2.5wt% and 0.03wt%, respectively) to obtain a nanoparticle dispersion, the first monomer solution and the second monomer solution are mixed, and the nanoparticle solution is added (the volume ratio of the first monomer solution, the second monomer solution, and the nanoparticle dispersion is 50:1:6), nitrogen is introduced into the reaction system to replace the air, an initiator of 5% of the mass of acrylamide is added (ferrous sulfate heptahydrate and 2,2'-azobis(2-methylpropionamidine) dihydrochloride are mixed in a mass ratio of 1:1), the temperature is raised to 60°C under a nitrogen atmosphere, and the polymerization reaction is carried out for 5h; after the reaction, the reaction solution is cooled to room temperature and filtered, and the precipitate is washed and set aside;

[0042] (4) Disperse 2.5 g of the washed precipitate in 50 ml of deionized water, add 2-aminobenzimidazole (5% of the mass of the precipitate), react at 80° C. for 3 h, cool to room temperature after the reaction, filter the reaction solution, wash the precipitate with ethanol and dry it to obtain an amphoteric polymer-coated nano zinc oxide material;

[0043] (5) dispersing the above-mentioned amphoteric polymer-coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecylbenzene sulfonate, and ultrasonically treating at 500W for 30min to obtain an activator solution, in which the concentrations of the amphoteric polymer-coated nano zinc oxide material, dodecyl glucoside, and sodium dodecylbenzene sulfonate are 0.2g / L, 0.152%, and 0.2%, respectively;

[0044] (6) The activator solution and the polycyclic aromatic hydrocarbon material are mixed in a volume ratio of 9:1, and ultrasonically treated at a power of 500 W for 30 minutes to obtain a polycyclic aromatic hydrocarbon material with high fluidity.

[0045] Example 3

[0046] A method for improving the fluidity of condensed aromatic hydrocarbon materials comprises the following steps:

[0047] (1) 2.95 g of thionyl chloride and 30 ml of DMF were mixed, and then a mixed solution consisting of 6.96 g of SDS and 40 ml of DMF was added, and the mixture was reacted at 5° C. for 12 h. After the reaction was completed, the reaction solution was washed several times with dichloromethane in ice water and dried, and the solvent was removed to obtain dodecylbenzenesulfonyl chloride;

[0048] (2) 7 g of dodecylbenzenesulfonyl chloride, 65 g of triethylamine and 5.5 g of diallylamine were dissolved in 50 ml of dichloromethane, and the mixture was stirred at room temperature and 700 rpm for 12 h. The reaction product was then washed with 1 wt % dilute hydrochloric acid solution, 1 wt % sodium hydroxide solution and saturated brine for multiple times, and the solvent was removed to obtain a functional monomer;

[0049] (3) Dissolve acrylamide (AM), sulfobetaine methacrylate (SBMA), and SDS in 50 ml of deionized water (the concentrations of AM, SBMA, and SDS are 1.5 mmol / ml, 0.15 mmol / ml, and 0.008 g / ml, respectively), and then adjust the pH to neutral to obtain a first monomer solution. Dissolve glycidyl methacrylate (GMA) and the above functional monomers in 10 ml of deionized water. DMSO (the concentrations of GMA and functional monomer are 0.03mmol / ml and 0.03mmol / ml respectively) is added to obtain a second monomer solution, nano zinc oxide and SDS are added to 50ml deionized water for stirring and emulsification (the concentrations of nano zinc oxide and SDS are 3wt% and 0.04wt% respectively) to obtain a nanoparticle dispersion, the first monomer solution and the second monomer solution are mixed, and the nanoparticle solution is added (the volume ratio of the first monomer solution, the second monomer solution and the nanoparticle dispersion is 50:1:5), nitrogen is introduced into the reaction system to replace the air, an initiator of 8% of the mass of acrylamide is added (ferrous sulfate heptahydrate and 2,2'-azobis(2-methylpropionamidine) dihydrochloride are mixed in a mass ratio of 1:2), the temperature is raised to 60°C under a nitrogen atmosphere, and the polymerization reaction is carried out for 6h; after the reaction, the reaction solution is cooled to room temperature and filtered, and the precipitate is washed and set aside;

[0050] (4) Dispersing 2 g of the washed precipitate in 50 ml of deionized water, adding 2-aminobenzimidazole (4% of the mass of the precipitate), reacting at 80° C. for 5 h, cooling to room temperature after the reaction, filtering the reaction solution, washing the precipitate with ethanol and drying, and obtaining an amphoteric polymer-coated nano zinc oxide material;

[0051] (5) dispersing the above-mentioned amphoteric polymer-coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecylbenzene sulfonate, and ultrasonically treating at 500W for 30min to obtain an activator solution, in which the concentrations of the amphoteric polymer-coated nano zinc oxide material, dodecyl glucoside, and sodium dodecylbenzene sulfonate are 0.25g / L, 0.15%, and 0.5%, respectively;

[0052] (6) The activator solution and the polycyclic aromatic hydrocarbon material are mixed in a volume ratio of 9:1, and ultrasonically treated at a power of 500 W for 30 minutes to obtain a polycyclic aromatic hydrocarbon material with high fluidity.

[0053] Example 4

[0054] A method for improving the fluidity of condensed aromatic hydrocarbon materials comprises the following steps:

[0055] (1) 2.95 g of thionyl chloride and 30 ml of DMF were mixed, and then a mixed solution consisting of 6.96 g of SDS and 40 ml of DMF was added, and the mixture was reacted at 5° C. for 12 h. After the reaction was completed, the reaction solution was washed several times with dichloromethane in ice water and dried, and the solvent was removed to obtain dodecylbenzenesulfonyl chloride;

[0056] (2) 7 g of dodecylbenzenesulfonyl chloride, 7 g of triethylamine and 6 g of diallylamine were dissolved in 50 ml of dichloromethane, and the mixture was stirred at room temperature and 1000 rpm for 12 h. The reaction product was then washed with 1 wt % dilute hydrochloric acid solution, 1 wt % sodium hydroxide solution and saturated brine for multiple times, and the solvent was removed to obtain a functional monomer;

[0057] (3) Dissolve acrylamide (AM), sulfobetaine methacrylate (SBMA), and SDS in 50 ml of deionized water (the concentrations of AM, SBMA, and SDS are 2 mmol / ml, 0.2 mmol / ml, and 0.01 g / ml, respectively), and then adjust the pH to neutral to obtain a first monomer solution. Dissolve glycidyl methacrylate (GMA) and the above functional monomers in 10 ml of deionized water. DMSO (the concentrations of GMA and functional monomers are 0.05mmol / ml and 0.05mmol / ml, respectively) is added to obtain a second monomer solution, nano zinc oxide and SDS are added to 50ml deionized water for stirring and emulsification (the concentrations of nano zinc oxide and SDS are 3wt% and 0.05wt%, respectively) to obtain a nanoparticle dispersion, the first monomer solution and the second monomer solution are mixed, and the nanoparticle solution is added (the volume ratio of the first monomer solution, the second monomer solution, and the nanoparticle dispersion is 50:1:7), nitrogen is introduced into the reaction system to replace the air, an initiator of 10% of the mass of acrylamide is added (ferrous sulfate heptahydrate and 2,2'-azobis(2-methylpropionamidine) dihydrochloride are mixed in a mass ratio of 1:1), the temperature is raised to 60°C under a nitrogen atmosphere, and the polymerization reaction is carried out for 6h; after the reaction, the reaction solution is cooled to room temperature and filtered, and the precipitate is washed and set aside;

[0058] (4) 3 g of the washed precipitate was dispersed in 50 ml of deionized water, 2-aminobenzimidazole (5% of the mass of the precipitate) was added, and the reaction was carried out at 80° C. for 3 h. After the reaction was completed, the reaction solution was cooled to room temperature, the reaction solution was filtered, and the precipitate was washed with ethanol and dried to obtain an amphoteric polymer-coated nano zinc oxide material;

[0059] (5) dispersing the above-mentioned amphoteric polymer-coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecylbenzene sulfonate, and ultrasonically treating at 500W for 20min to obtain an activator solution, in which the concentrations of the amphoteric polymer-coated nano zinc oxide material, dodecyl glucoside, and sodium dodecylbenzene sulfonate are 0.3g / L, 0.2%, and 0.5%, respectively;

[0060] (6) The activator solution and the polycyclic aromatic hydrocarbon material are mixed in a volume ratio of 9:1, and ultrasonically treated at a power of 500 W for 30 minutes to obtain a polycyclic aromatic hydrocarbon material with high fluidity.

[0061] The activator solution prepared in the above embodiment was placed at 0°C, 25°C and 70°C for 7 days, 7 days and 24 hours respectively, and the stratification of the solution was observed to determine the stability of the activator solution. The test results are shown in Table 1.

[0062] Table 1

[0063]

[0064]

[0065] Application Examples

[0066] The activator solutions prepared in Examples 1-4 were mixed with Daqing 0# diesel at a volume ratio of 9:1, and ultrasonicated for 30 min at a power of 500 W to obtain an emulsion. The viscosity was measured according to the national standard "GB / T265-1988 Petroleum Product Kinematic Viscosity Determination Method and Dynamic Viscosity Calculation Method" using a SYA-265B Petroleum Product Kinematic Viscometer, and the viscosity reduction rate was calculated.

[0067] Viscosity reduction rate (%) = (η 0 -η 1 ) / η 0 ×100%;

[0068] Among them, η 0 is the original viscosity of diesel; η 1 is the viscosity of biodiesel after modification with activator solution. The test results are shown in Table 2.

[0069] Table 2

[0070] Viscosity reduction rate, % Example 1 98.5 Example 2 98.3 Example 3 98.5 Example 4 98.7

[0071] The emulsifier solution prepared in the above application example was stored at 5° C. and 30° C. for 7 days respectively, and the stratification was observed. The test results are shown in Table 3.

[0072] Table 3

[0073] 5℃, 7 days 30℃, 7 days Example 1 No stratification No stratification Example 2 No stratification No stratification Example 3 No stratification No stratification Example 4 No stratification No stratification

[0074] It can be seen from the above test results that the activator solution prepared by the present invention has good stability and can effectively reduce the viscosity of biodiesel, thereby improving the fluidity of biodiesel, and the emulsifier solution prepared by adding it to biodiesel has good stability.

[0075] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for improving the fluidity of condensed aromatic hydrocarbon materials, characterized in that: The following steps are involved: (1) reacting a DMF solution of thionyl chloride with a DMF solution of SDBS in a reactor. After the reaction is completed, washing the reaction solution multiple times in an ice water bath, and then drying and removing the solvent to obtain dodecylbenzenesulfonyl chloride; (2) dissolving dodecylbenzenesulfonyl chloride, triethylamine and diallylamine in dichloromethane, stirring for reaction, then washing the reaction product several times, and removing the solvent to obtain a functional monomer; (3) dissolving acrylamide, sulfobetaine methacrylate and SDS in deionized water, and then adjusting the pH thereof to be neutral to obtain a first monomer solution, dissolving glycidyl methacrylate and the above functional monomer in DMSO to obtain a second monomer solution, adding nano zinc oxide and SDS into deionized water, stirring and emulsifying, to obtain a nanoparticle dispersion, mixing the above first monomer solution and the second monomer solution, and adding the above nanoparticle solution, introducing nitrogen into the above reaction system to replace the air, adding an initiator, and heating the reaction system under a nitrogen atmosphere for polymerization reaction; after the reaction is completed, cooling the reaction solution to room temperature and filtering it, washing the precipitate, and setting it aside; (4) dispersing the washed precipitate in deionized water, adding 2-aminobenzimidazole, and reacting. After the reaction is completed, cooling to room temperature, filtering the reaction solution, washing the precipitate, and drying it to obtain an amphoteric polymer-coated nano zinc oxide material; (5) dispersing the above-mentioned amphoteric polymer-coated nano zinc oxide material in deionized water, adding dodecyl glucoside and sodium dodecylbenzene sulfonate, and ultrasonically treating to obtain an activator solution, and mixing the above-mentioned activator solution with a polycyclic aromatic hydrocarbon material and ultrasonically treating to obtain a polycyclic aromatic hydrocarbon material with high fluidity.

2. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (1), the mass ratio of thionyl chloride to SDBS is (2-3): (6-10).

3. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (1), the reaction temperature is 5°C and the reaction time is 10-15h.

4. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (2), the mass ratio of dodecylbenzenesulfonyl chloride, triethylamine and diallylamine is (5-8): (6-7): (5-6).

5. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (2), the stirring reaction temperature is room temperature, the stirring speed is 500-1000 rpm, and the time is 10-15 hours.

6. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (3), the concentrations of acrylamide, sulfobetaine methacrylate and SDS in the first monomer solution are 1-2 mmol / ml, 0.1-0.2 mmol / ml and 0.005-0.01 g / ml respectively; the concentrations of glycidyl methacrylate and functional monomer in the second monomer solution are 0.02-0.05 mmol / ml and 0.02-0.05 mmol / ml respectively; the concentrations of nano zinc oxide and SDS in the nanoparticle dispersion are 2-3 wt% and 0.01-0.05 wt% respectively; the volume ratio of the first monomer solution, the second monomer solution and the nanoparticle dispersion is 50:1:(5-10).

7. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (3), the initiator is a mixture of ferrous sulfate heptahydrate and 2,2'-azobis(2-methylpropionamidine) dihydrochloride, the mass ratio of the two being 1:(1-2); the amount of the initiator added is 5-10% of the mass of acrylamide.

8. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (3), the temperature of the polymerization reaction is 55-65° C. and the time is 5-6 hours.

9. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (4), the amount of 2-aminobenzimidazole added is 3-6% of the mass of the precipitate, the reaction temperature is 75-85° C., and the reaction time is 2-5 h.

10. A method for improving the fluidity of condensed aromatic hydrocarbon materials according to claim 1, characterized in that: In step (5), in the activator solution, the concentrations of the amphoteric polymer-coated nano zinc oxide material, dodecyl glucoside, and sodium dodecylbenzene sulfonate are 0.2-0.3 g / L, 0.1-0.2%, and 0.1-0.5%, respectively; and the volume ratio of the activator solution to the polycyclic aromatic hydrocarbon material is (9-10):1.

Citation Information

Patent Citations

  • Agent for improving low temp. flowability of diesel

    CN1358826A

  • Flowability improver for crude oil and its preparing process

    CN1376757A